Is transurethral needle ablation of prostate out of fashion? Outcomes of single session office-based transurethral needle ablation of prostate in patients with symptomatic benign prostatic hyperplasia - Law, Y.X.T. (Korean Urological Association, 2021)
10.4111/icu.2019.60.5.351